The Role of MSMEs in Driving Sustainable Development in Indonesia - Azzahra, Raisa Nadira; Larasati, Prita; Rizki, Muhammad; Priyono, Budi (KnE Social Sciences, 2025)
Micro, Small and Medium Enterprises (MSMEs) have an important role in driving economic growth in Indonesia. In today’s era of rapid change, diversification and digitalization are effective methods that can be implemented by MSMEs to overcome unexpected market change and are a framework for a sustainable economy. This study aims to determine the role of MSMEs in driving sustainable development in Indonesia as a form of achievement in the implementation of Sustainable Development Goals. It uses a qualitative descriptive method with document study techniques in collecting data. Data analysis is carried out by collecting, compiling, and interpreting data then arriving to conclusions. Results show that expanding diversification is one way that MSMEs can increase their competitiveness. As one of the pillars of economic growth in Indonesia, MSMEs must develop so that they can increase their competitiveness in the global arena to encourage sustainable development in the era of national transformation. In addition, carrying out digital transformation also needs to be implemented to encourage sustainable development in Indonesia.